THE NEED TO DEVELOP PEDAGOGICAL THINKING IN FUTURE TEACHERS - Shaydullayeva Kamola Shapulatovna (American Journals, 2025)
The article summarizes theoretical and practical research and offers a new solution to the problem of improving the quality of training of future teachers identified in creating psychological and pedagogical conditions for the development of their effective pedagogical thinking. The article analyzes the principles, methods, stages and means of implementing the psychological-pedagogical conditions for the development of effective pedagogical thinking. We have determined the main levels of maturity of effective pedagogical thinking in the process of mastering higher education subjects of future teachers.
Keywords: Pedagogical thinking, pedagogical-psychological condition, discussion network, professional activity, flexible thinking, psychological-pedagogical criteria, visualization, critical thinking.